Cerebral Small Vessel Disease Burden Related to Carotid Intraplaque Hemorrhage Serves as an Imaging Marker for Clinical Symptoms in Carotid Stenosis - Fan, Xiaoyuan; Zhang, Xiaoqian; Lai, Zhichao; Lin, Tianye; You, Hui; Liu, Changwei; Feng, Feng (Frontiers in Neurology, 2021)
Objectives: In patients with carotid stenosis, to investigate the relationship between carotid intraplaque hemorrhage (IPH) and total burden of cerebral small vessel disease (CSVD), and preliminarily explore whether the total CSVD burden as an imaging marker can distinguish the severity of clinical symptoms. Methods: A total of 108 patients (mean age was 66 ± 7 years, and 85.2% were male) with unilateral carotid stenosis ≥ 50% underwent brain MRI and high-resolution MRI for carotid plaque characterization. The total burden of CSVD was calculated by accumulating one point according to the presence or severity of each of the four MRI markers: white matter hyperintensities, lacunes, perivascular spaces and cerebral microbleeds. Recent clinical symptoms including transient ischemic attack, amaurosis fugax and ischemic stroke were recorded. The association between IPH and total CSVD burden was examined adjusted for other risk factors. The symmetry of CSVD burdens between ipsilateral and contralateral hemispheres of IPH was tested. Imaging features (CSVD score, IPH, degree of stenosis and completeness of circle of Willis) were correlated with clinical symptoms by Kruskal-Wallis H test, Chi-square test and Fisher's exact test. Results: Multivariable logistic regression analysis showed IPH (OR = 2.98, 95% CI [1.39, 6.40], p = 0.005) was independently associated with a higher CSVD score. The presence of unilateral IPH was associated with the inter-hemispheric CSVD score difference (p = 0.004). Patients with stroke had higher ipsilateral CSVD score than asymptomatic patients (p = 0.004) and those with transient ischemic attack/amaurosis fugax (p = 0.008). The statistical difference was marginally significant between symptoms and IPH (p = 0.057). No statistical difference was found between symptoms and degree of stenosis, and completeness of circle of Willis (p > 0.05). Conclusions: Carotid IPH is associated with an elevated total burden of CSVD in patients with carotid stenosis. Compared with the degree of stenosis, primary collaterals and IPH, the total CSVD score might be a more effective imaging marker linked with clinical symptoms.